A facile fabrication of zinc oxide‐doped carbon aerogel by cellulose extracted from coconut peat and sodium alginate for energy storage application. Issue 19 (8th March 2023) - Duy, Pham Hoang Anh; Tu, Phan Minh; Son, Tran Thanh; Dat, Nguyen Minh; Nam, Nguyen Thanh Hoai; Cong, Che Quang; Hai, Nguyen Duy; An, Hoang; Huyen, Nguyen Thi Thanh; Minh, Phan Pham Duc; Son, Nguyen Truong; Phong, Mai Thanh; et al.
Abstract: In this study, ZnO‐doped carbon aerogel is synthesized from cellulose in coconut peat with sodium alginate as a binder via both freeze‐drying and pyrolysis processes. Of those, zinc nitrate is used as not only a crosslinking agent to form gel but also a precursor source to dope ZnO in the carbon aerogel matrix. The effect of precursor ratios on the characterization and energy storage capacity of composite aerogel is investigated. As a result, it is indicated that the formed ZnO‐doped carbon aerogel possesses a highly porous structure which is typical for aerogel structure shown by SEM images, density, and porosity. Besides, via the XRD patterns, the confirmation of the ZnO crystal structure is found within the carbon aerogel lattice. In terms of energy storage, based on the specific capacitance results, the ZCA‐4 sample with a sodium alginate and cellulose weight ratio of 1:20 shows the best energy storage with a specific capacitance of 105 F/g in the voltage range of 0–0.5 V and scan‐rate speed of 0.005 V. Therewithal, the ZCA‐4 also performs high durability, high scanning speed tolerance, and stable storage performance with efficiency reaching more than 99% after 500 consecutive scan cycles. These results demonstrate that the ZnO‐doped carbon aerogel has potential applications as electrode materials in supercapacitors. Abstract :